Employee Stock Ownership Program (ESOP) Sebagai Perencanaan Keuangan Jangka Panjang bagi Karyawan Bank Central Asia - Malang - T. Renald Suganda; Dian Wijayanti; Uki Yonda Asepta (Jurnal ABM Mengabdi, 2017)
Employee Stock Ownership Program (ESOP) is a program that allows employee participation to own company or parent company shares where they work. One of the companies that implement ESOP is Bank Central Asia (BCA) which has 25,023 employees as a whole. Employees who get ownership of these shares need to be equipped with how to manage them considering that the stock is a capital market product intended for long-term investment. Assistance for BCA employees is implemented with the aim of improving the understanding of bank employees on capital market instruments, especially stocks. This activity was held in BCA Kanwil VII Malang, attended by 53 participants. The workshop and public education methods were carried out through several meetings with the subjects presented are Aspects of Going Concern, Introduction to Capital Market and Access to Market Data, Analysis of Capital Market Instruments, and Stock Trading Mechanism in Indonesia through D'ONE Trade Pro software. This devotion program is implemented by involving three parties namely the Indonesia Stock Exchange (BEI), Universitas Ma Chung, and PT Danareksa Sekuritas as one of the IDX listed members. The results of this program are among others increased employee understanding of investment in the capital market as long-term financial planning and employees become investors who are proactive and sophisticated in making decisions.